Translation Techniques used by Accounting Students in Writing Abstracts - Arief Zul Fauzi (Faculty of Economics, Law, and Humanities, 2022)
This study discusses the translation techniques used by students in the abstract part of the final project from Indonesian into English by using the translation techniques of Molina and Albir. This study used a qualitative evaluation to study the results of the analysis of translation techniques. In this study, the data collected by the researchers chose the abstracts that were present in the 50 final projects abstract text of the Associate Degree (Diploma 3) Accounting Study Program in Politeknik Harapan Bersama year 2021 with a simple random sample technique of data collecting method for all students. The abstract was then analyzed and classified based on translation techniques based on Molina and Albir's classification (2002). The data was calculated to find the dominant translation technique. Finally, the authors report the findings that there are 247 analyzed data found from Indonesian to English. From 18 translation techniques from Molina and Albir, the translator found 5 different techniques. The analysis findings are as follows: Translation techniques found in the abstract: literal 190 times, borrowing 33 times, calque 10 times, adaptation 10 times, and compensation 4 times. Based on the above findings, the translation technique used by many translators in the translation of abstract texts in the final project is a literal translation.